2016
DOI: 10.1111/psyp.12615
|View full text |Cite
|
Sign up to set email alerts
|

The role of top‐down spatial attention in contingent attentional capture

Abstract: It is well known that attentional capture by an irrelevant salient item is contingent on top-down feature selection, but whether attentional capture may be modulated by top-down spatial attention remains unclear. Here, we combined behavioral and ERP measurements to investigate the contribution of top-down spatial attention to attentional capture under modified spatial cueing paradigms. Each target stimulus was preceded by a peripheral circular cue array containing a spatially uninformative color singleton cue.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
28
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 46 publications
7
28
1
Order By: Relevance
“…Though our study (Huang et al, 2016) provided electrophysiological evidence that top-down spatial attention could modulate contingent attentional capture, the underlying mechanism is still not clear. One possibility is that the modulation effect was caused by spatial relevance of cues.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…Though our study (Huang et al, 2016) provided electrophysiological evidence that top-down spatial attention could modulate contingent attentional capture, the underlying mechanism is still not clear. One possibility is that the modulation effect was caused by spatial relevance of cues.…”
Section: Introductionmentioning
confidence: 75%
“…Our recent ERP study (Huang, Su, Zhen, & Qu, 2016) further provided the first electrophysiological evidence for the modulation of top-down spatial attention on contingent attentional capture. We utilized variants of spatial cueing paradigms and compared the spatial cueing effects and cue-elicited N2pcs under different manipulations of top-down spatial attention.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Such capture of attention is often called contingent attentional capture (Folk et al, ), and the supporting evidence usually comes from studies using a spatial cueing paradigm or a rapid serial visual presentation (RSVP) paradigm in which irrelevant‐but‐salient cues are presented about 200 ms before the target. For example, numerous behavioral and ERP studies using a spatial cueing paradigm (Eimer & Kiss, ; Folk et al, ; Folk, Remington, & Wright, ; Huang, Su, Zhen, & Qu, ; Kiss & Eimer, ; Lien, Ruthruff, & Cornett, ) or an RSVP paradigm (Folk, Leber, & Egeth, , ; Huang et al, ; Leblanc, Prime, & Jolicoeur, ; Moore & Weissman, ; Serences et al, ) found that irrelevant color singleton cues attracted attention (reflected by delaying target detection and/or eliciting an involuntary N2pc component) when the target was also defined by color. According to goal‐driven theories, the finding in the additional singleton paradigm that a color singleton distractor captured attention was probably due to the use of an attentional set that favors any type of feature singleton rather than a specific feature value (called singleton‐detection mode; Bacon & Egeth, ).…”
Section: Introductionmentioning
confidence: 99%